Impact of cold plasma treatment on nutritional, antinutritional, functional, thermal, rheological, and structural properties of pearl millet flour. (15th March 2023) - Sarkar, Ayan; Niranjan, Thota; Patel, Gopesh; Kheto, Ankan; Tiwari, Brijesh K.; Dwivedi, Madhuresh
Abstract: This study was planned to investigate the effect of atmospheric cold plasma (CP) treatment at different power levels (20–30 kV) for 10–20 min on physicochemical, technofunctional, and intermolecular changes of pearl millet flour (PMF). It was observed that exposure to plasma significantly modified the sample's proximate, antinutritional, functional, thermal, rheological, and morphological properties. A concomitant ( p < 0.05) decreases in antinutritional factors (tannin and phytic acid) was noticed in CP‐treated PMF compared to the control sample. Maximum reduction in tannin and phytic acid was observed at 30 kV for 20 min‐treated PMF. However, scanning electron microscopy revealed significant changes in flour starch granular structure, while decreases in relative crystallinity were also observed in CP‐treated samples from 23.45% to 19.31%. In addition, an increase in water absorption capacity (1.32–1.62 g/g), oil absorption capacity (1.11–1.31 g/g), emulsifying capacity (EC; 86.58%–91.25%) and foaming capacity (FC; 10.67–12.84%), as well as a decrease in pH (7.83–6.97) were found at 30 kV for 20 min. Apart from this, high intensity CP‐treated samples showed shear thinning behavior. At the same time, the power–law model was more appropriate for determine the flow behavior index ( n ) and consistency coefficient ( k ). On the other hand, CP‐treated samples exhibit higher storage modulus values ( G ′), indicating an elastic response. Based on the observations, the 30 kV‐20 min‐treated sample could be used for product formulation, contains lower antinutritional factors and retaining the nutritional components and functional properties. Practical applications: This work has identified that exposure to cold plasma improved the physicochemical, rheological, thermal, and functional properties of pearl millet flour with considerably reducing its antinutritional content, which can be helpful for various food industries. This possibly will encourage its application in the development of various food products, (like cookies, biscuits, bread, beverages, etc.) chiefly as a functional food ingredient. Abstract : Cold plasma treatment on nutritional, antinutritional, functional, thermal, rheological, and structural properties of pearl millet flour.